Kepemimpinan Perempuan dalam Perspektif Islam - Raihan Putry (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2015)
Leadership is no longer based on talent, ancestry, experience and male gender alone, but more than that physical and mental readiness of men and women in a planned towards professionalism. All the program is done through planning, analysis and development systematically to raise stamina attributes. Leadership in accordance with the spirit of the Shari'ah.